Usage of permeability ratio to check the stability of a pile-soil model with retaining wall support – Huizhou slope failure as a case study - Muhammad Israr Khan; Jianbo Fei; Xiangsheng Chen; Yue Chen (International Journal of Geo-Engineering)
Abstract This paper presents a comprehensive investigation into the role of soil permeability variation on the stability of slopes reinforced by retaining walls, with a focus on the Huizhou slope failure as a case study. The study demonstrates that rising groundwater levels diminish the Factor of Safety (FoS) for retaining walls, with stability most compromised under combined loading from adjacent soil and lightweight concrete. These findings emphasize the need for enhanced drainage or structural support in retaining wall designs subjected to elevated groundwater conditions. It integrates advanced numerical simulations, utilizing Abaqus and GeoStudio, with empirical field data to analyze the interactions between soil permeability, pore water pressure, moisture content, shear strength, and the overall stability of the slope. The dynamics of water infiltration are influenced by permeability, moisture content, and the groundwater table. These factors change the pore pressure and decrease shear strength, which causes shear failure in the slope mass. This research also looks at how surcharge loading affects slope stability. Higher permeability soils cause faster infiltration rates, leading to higher pore pressures, lower effective shear strengths, and a higher likelihood of slope failure. The opposite is true for reduced permeability, which makes drainage more difficult and ultimately leads to hydrostatic pressure building up behind retaining walls, which in turn makes the slope even more unstable. This study demonstrates the critical need for optimized drainage systems to reduce the hazards of infiltration-induced failure and the role of precise permeability evaluation in geotechnical design. Geotechnical engineers can use these results to better understand how to construct and maintain slope stabilization systems.